1996
DOI: 10.1016/s0092-8674(00)80161-0
|View full text |Cite
|
Sign up to set email alerts
|

Interchromosomal Transfer of Epigenetic States in Ascobolus: Transfer of DNA Methylation Is Mechanistically Related to Homologous Recombination

Abstract: The transfer of methylation between alleles represents a plausible epigenetic mutational mechanism to explain loss of imprinting in mammals and paramutation in plants. Here, we have exploited advantages unique to the fungus Ascobolus immersus to obtain direct experimental evidence that methylation transfer can occur between homologous chromosomes. A methylated allele and an unmethylated allele of the Ascobolus b2 spore color gene were brought together in individual meiotic cells. Frequent transfer of methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 46 publications
3
61
1
Order By: Relevance
“…One implication of these findings is that gene body methylation, which is an ancestral property of eukaryotic genomes (24,25), could protect genome integrity by inhibiting supernumerary COs within exons. On a similar note, it has been shown that the controlled addition of DNA methylation leads to a decrease in meiotic recombination for a particular locus in Ascobulus (26,27).…”
Section: Discussionmentioning
confidence: 83%
“…One implication of these findings is that gene body methylation, which is an ancestral property of eukaryotic genomes (24,25), could protect genome integrity by inhibiting supernumerary COs within exons. On a similar note, it has been shown that the controlled addition of DNA methylation leads to a decrease in meiotic recombination for a particular locus in Ascobulus (26,27).…”
Section: Discussionmentioning
confidence: 83%
“…The loxP-mediated silencing in the mouse 58 (BOX 5) is reminiscent of the transfer of methylated sequences that occurs during recombination in Ascobolus immersus 61 . Here, transfer of DNA methylation from a methylated allele to an unmethylated allele of the b2 spore-colour gene occurred when the two alleles were together in meiotic cells.…”
Section: Evolution Of Polyploidsmentioning
confidence: 99%
“…It has been proposed that DNA methylation, in addition to its repressive e ects on transcription, may suppress homologous recombination between repetitive elements in the genome (Colot and Rossignol, 1999). Work with the fungus Ascobolus immersus, provides evidence that DNA methylation can suppress recombination (Colot et al, 1996). Increased genomic instability seen in the hypomethylated genome of embryonic stem cells lacking Dnmt1 provides evidence for a genome protective capacity for methylation (Chen et al, 1998).…”
Section: Disruption Of Epigenetic States In Cancermentioning
confidence: 99%